The impact of teaching about the nature of science in a senior high school in China - Shi, Xiaoming (2020)
The purpose of this study was to observe the impact of a programme of teaching about the Nature of Science on high school students and teachers, and consider the implications of the findings for school science education in China. Since 2018, there has been a national requirement to teach the concept of Hexin Suyang (核心素养). By comparing Hexin Suyang in science with the concepts, widely adopted internationally, of scientific literacy and the nature of science, this research identifies significant conceptual commonalities. These commonalities were drawn upon to design and develop a Nature of Science course suitable for Chinese high school students. This practitioner research study employs mixed methods, a modified version of the Views on Science and Technology questionnaire (Aikenhead & Ryan, 1992) and phenomenography, to study the high school students' understandings of science before and after the course and to record the changes in students and teachers during the lessons. The study concludes that the new Nature of Science curriculum had a significant impact on students' scientific cognition, supported learning about Hexin Suyang and helped teachers develop interdisciplinary pedagogies. It identifies the differences between the Nature of Science approach and traditional Chinese science education and proposes further curriculum development and reform.